Beyond the Organic Paradigm Biomorphic Digital Architecture - Barison, Marcello (Aesthetica Preprint, 2021)
This paper aims at a definition of the biomorphic paradigm that characterizes a significant part of contemporary architecture. This paradigm is clearly distinguished from the classical organic paradigm as it was initially outlined by F. L. Wright and represents a considerable development that must therefore be addressed in a specific way. The paper will be structured in three distinct sections, organized as follows: 1. Conceptual definition of the organic paradigm, with main focus on the work of Frank Lloyd Wright. 2. Conceptual definition of the biomorphic paradigm in light of the overcoming of the classic organic model, in order to set a clear distinction between the idea, typical of the organic model, of integrating architecture and the natural environment, and that, here presented moving from a reference to Niemeyer’s work, of an architecture capable in itself to expresses a natural morphology. 3. Contemporary developments in biomorphic natural architecture, demonstrating how the reproduction of natural morphology in the construction sector has undergone an extraordinary increase with the development of modern digital technologies.